Towards a New Continuous Improvement Organization Based on Simulation. Issue 4 (2nd October 2022) - Alencar de Paula, Rafael; Mosbah, Abdallah Ben; Chinniah, Yuvin; Bassetto, Samuel
Abstract: The paper proposes a mathematical model to forecast the time needed during a continuous improvement (CI) project. To do this, the authors adapted the famous Lotka–Volterra model to the CI methodology. Also, the authors examined a Montreal company's database to simulate the CI's necessary time in the real world. Firstly, the model simulates a total of CI hours for the employees and the respective quantity of problems at the end of the project. And after, the authors compared the simulation results with the project real results. This work introduces a new model to forecast the CI's necessary time and discuss an innovative way to implement a CI project. This work also considers the advantages and difficulties of achieving a CI project based on a simulation. One of the work's main result is the discussion of the total CI hours performed by the employees: 130% of the simulation proposition. This quantity of hours leads to half of the problems estimated by the model: 42%. The normalized results showed a difference of 1.03% between the simulation and the observations in the real world.